Clinical evaluation of a 31‐year‐old woman with crural monomelic amyotrophy - Thompson, Austin R. (Clin Case Rep, 2019)
This report describes the clinical presentation of a female patient diagnosed with crural MMA. Careful clinical correlation is necessary to distinguish crural MMA from other motor neuron diseases. When crural MMA is diagnosed, treatment options aim to alleviate symptoms.